NEXUS BETWEEN BELIEFS COLLEGE ENGLISH INSTRUCTORS’ HELD ABOUT TEACHING READING STRATEGIES AND THEIR CLASSROOM PRACTICE - Chanyalew Enyew; Solomon Melesse (Istraživanja u Pedagogiji, 2018)
This study examined connections between beliefs college English language instructors’ held about reading strategies and how they implemented them in teaching reading. The sites of the target population for this study were the Colleges of Teacher Education students in Amhara National Regional State Council, Ethiopia. In this region, there are 10 Administrative Zones. In the zones, there are 10 colleges. Among these, 4 colleges were selected by simple random sampling technique. From the 4 selected colleges, 26 instructors were selected by simple random sampling technique. Data were collected through close-ended questionnaire items and observation checklist. Data obtained from questionnaire were analyzed using percentage where the observation data were applied one sample t-test. The findings indicate that college instructors held strong beliefs about English language strategies. In spite of their strong belief, however, the research confirmed that instructors do not actually apply the strategies in their reading classes. From the findings, it could be inferred that it would be useful if instructors adjust their beliefs to practices. To help instructors connect their beliefs to their practice, there seems a need to train them on reading strategies.